The Role of Cocoa Commodity as a Base Sector in Indonesia’s Regional Development - Adyanti, Amanda Sekar; Aji, Joni Murti Mulyo; Hani, Evita Soliha (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Indonesia’s cocoa commodity as one of the leading commodities, has the potential to improve the country’s economy. However, the increasing export volume is not matched by the decreasing production due to the decreasing land area. This study aims to identify the mapping of cocoa regions, identify the structure and growth rate of cocoa, and examine the role of cocoa in supporting Indonesia’s plantation activities. The research was conducted in 33 provinces of Indonesia using secondary data. The variables used are production and revenue of cocoa and plantation commodities in 2017-2023. The analytical tools used are Location Quotient (LQ), Dynamic Location Quotient (DLQ), Localisation and Specialisation analysis, Shift Share analysis (SSA), BSR analysis, RM, and Multiplier Effect. The results obtained from as many as 19 provinces are included in the base area with an LQ>1 value. The cocoa growth rate structure obtained that the value of National growth (PNij) is positive, Proportional growth (PPij) is negative, and Regional share growth (PPWij) is negative, so the average shift share value is positive and it is said that Indonesian cocoa is growing. The results of the analysis of the value of BSR, RM, and Multiplier Effect are positive so that Indonesian cocoa plays a role in supporting Indonesian plantations.